Tailoring the Porosity in Iron Phosphosulfide Nanosheets to Improve the Performance of Photocatalytic Hydrogen Evolution. Issue 12 (6th June 2019) - Zhang, Jian; Feng, Fang; Pu, Yong; Li, Xing'ao; Lau, Cher Hon; Huang, Wei
Abstract: Metal sulfide photocatalysts are typically required during water splitting to produce hydrogen. However, the rapid recombination of photogenerated electron–hole pairs in these highly unstable photocatalysts has restricted hydrogen production to small‐scale batch reactions. In this work, porous transition‐metal thiophosphites were used to enable continuous long‐term hydrogen production through photocatalysis. A wide bandgap (2.04 eV) was essential for generating hydrogen at a rate of 305.6 μmol h −1 g −1, 180 % faster than nonporous FePS3 nanosheets. More importantly, the high in‐plane stiffness of these approximately 7 nm thick porous FePS3 nanosheets ensured structural stability during 56 h of continuous photocatalysis reactions. The reaction results with D2 O instead of H2 O indicated that hydrogen mainly came from H2 O. Furthermore, a sacrificial reagent (triethylamine) was photodegraded into diethylamine and acetaldehyde through a monoelectronic oxidation process, as indicated by HPLC and LC–MS. This synthesis strategy reported for FePS3 porous nanosheets paves a new pathway for designing other dianion‐based inorganic nanocrystals for hydrogen energy applications. Abstract : Get under the nanosheets ! The porosity in iron phosphosulfide nanosheets can be tailored to improve the stability and efficiency of photocatalytic hydrogen evolution. Continuous long‐term hydrogen production was achieved owing to the wide bandgap (2.04 eV) and hydrogen was generated at a rate of 305.6 μmol h −1 g −1, which was 180 % faster than nonporous FePS3 nanosheets.